The development and evaluation of a sequential aerosol-water measurement system. (1st November 2021) - Sun, Shao-En; Chang, Shih-Yu; Lee, Chung-Te
Abstract: Aerosol water content (AWC) is associated with aerosol formation, aerosol–cloud interaction, and atmospheric visibility degradation; however, few studies have directly measured the mass of water in aerosols. Studies on AWC have employed modeling techniques [e.g., ISORROPIA II and the Extended Aerosol Inorganics Model (E-AIM) III)], the thermal-ramp Karl-Fisher method, and conducted volume-based measurements by using a hygroscopic tandem differential mobility analyzer (H-TDMA). The current study developed a sequential aerosol-water measurement system (SAWMS) that sequentially collects particles with up to 10 filters and measures AWC immediately after the collection. With this system, the loss of semi-volatile species was lower, and contamination during sample transport was reduced. The AWC measurement results were validated by comparing them with modeling results obtained in this study and the results obtained in previous studies. The measurement results for three aerosolized salts—NaCl, NH4 NO3, and (NH4 )2 SO4 —were found to be in favorable agreement with the corresponding modeling results and results from previous studies. The relationship between aerosol mass change (AMC) and relative humidity (RH) was investigated. The deliquescence RH (DRH) was 75%, 63%, and 81% for NaCl, NH4 NO3, and (NH4 )2 SO4, respectively, whereas efflorescence RH was observed only for NaCl at 40%–50% RH. The AWC of mixed inorganic salts exhibited weak mutual DRH at 45%–50% RH. By contrast, the AWC obtained using ISORROPIA II and E-AIM III exhibited a gradual rather than an abrupt change of RH upon deliquescence. The measured AWC values were more similar to the values obtained with ISORROPIA II than to the values obtained with E-AIM III. To compare our mass-based measurements with the volume-based measurements obtained in previous studies using H-TDMAs, we derived the relationships of hygroscopicity parameter and growth factor with AMC. We discovered that the aforementioned relationships were comparable. In summary, the developed SAWMS integrates a sequential aerosol collection device with a gas chromatograph equipped with a thermal conductivity detector; the system performs well in the quantification of AWC and provides an additional chance of the filter for further chemical analysis. Graphical abstract: Image 1 Highlights: A system was developed for measuring aerosol water mass sequentially. The single salt measurements were comparable to thermodynamic model results. The measured and modeled humidographs of the mixed salt were consistent. The derived hygroscopicity factors agreed with other in-situ measurements.